Applying educational theory to develop a framework to support the delivery of experiential entrepreneurship education. Issue 6 (2nd October 2020) - Bell, Robin; Bell, Heather
Abstract : Purpose: Experiential approaches have become increasingly common in entrepreneurship education in response to calls for different approaches to the traditional didactic process-driven approach. Experiential approaches offer the potential to develop the skills and mindset that are required in entrepreneurship. Research has highlighted the critical importance of educator pedagogical competence in the delivery and quality of teaching and learning in further and higher education. Nevertheless, educator narratives and practices are often based on foundations that suggest a lack in the depth of knowledge and understanding of the underlying pedagogic learning theories and practice. This paper brings educational theory and pedagogic practice together in a three-stage framework of the experiential entrepreneurship learning process to support entrepreneurship educators within further and higher education. Design/methodology/approach: This paper reviews and brings together the seminal educational theories and philosophies of constructivism, objectivism, Kolb's (1984) theory of experiential learning, Schön's (1983) reflection-in-action and Mezirow's (1997) theory of transformative learning, to develop a framework which underpins the experiential entrepreneurship learning process. Findings: This paper develops a three-stage framework which informs the roles of an educator and a learner in experiential entrepreneurship education within further and higher education, based on educational theories and philosophies that inform the learning process. Practical implications: The developed framework supports the pedagogic competence of educators in the delivery of experiential entrepreneurship education through a deeper understanding of the supporting theory that informs the pedagogic practice. This will provide consolidation to enable educators to maximise the effectiveness of their educational practice (Kaynardağ, 2019) and can increase the legitimacy of entrepreneurship education (Foliard et al., 2018). Originality/value: This paper meets calls in the literature to provide a closer engagement between educational theory and pedagogic practice to afford guidance as to how educators can navigate some of the different educational theories and philosophies to consolidate the effective delivery of quality experiential entrepreneurship education. Applying seminal educational theories and philosophies to ensure the quality of experiential education can support the legitimacy of experiential entrepreneurship education.